Modeling residents’ multidimensional social capital in China’s neighborhood renewal projects: SEM and MIMIC approaches - Huang, Ruopeng; Xie, Fangyun; Fu, Xinyue; Liu, Wenli (Frontiers in Psychology, 2023)
Neighborhood renewal is now an important approach to sustainable urban development in China. However, neighborhood renewal projects are often beset with social problems such as noncooperation from residents, which can be attributed to diverse interests and complex relationships among residents. However, there is little research on resident relations in China and intra-resident conflict. Based on social capital, this study provided a better understanding of resident relationships in neighborhood renewal in China. To this end, we developed a theoretical framework of residents’ multidimensional social capital (structural, relational, and cognitive). Then, a survey was conducted to collect data from 590 residents across China who were experiencing or had experienced neighborhood renewal. Structural equation modeling (SEM) and multiple indicators multiple causes (MIMIC) modeling were used. The results revealed positive effects of structural social capital on relational and cognitive social capital, and the mediation role of relational social capital was demonstrated. We also tested the effects of differences in sociodemographic characteristics. Our findings verify the explanatory power of social capital regarding residents’ complex relationships in neighborhood renewal in China. Implications for theory and policy are discussed. This study helps to improve our understanding of residents’ social systems in neighborhood renewal and provides theoretical support for formulating neighborhood renewal policies in China and abroad.